The Role of Customer and Market Orientation in Enhancing Islamic Insurance Performance: Evidence from Tunisia - Gafsi, Nesrine (Journal of Ecohumanism, 2025)
Purpose: This study investigates the impact of customer orientation, market orientation, and inter-functional coordination on the performance of Islamic insurance companies in Tunisia. Methodology: A quantitative research design was adopted, using the Partial Least Squares (PLS) method. Data were collected through a survey of 133 employees from three Islamic insurance companies in Tunisia. Results: The study confirms the positive influence of customer and market orientation on the performance of Islamic insurance companies. It also highlights the crucial role of inter-functional coordination in improving organizational performance. Originality: This research stands out by simultaneously applying these three strategic variables to the specific sector of Islamic insurance in Tunisia. Few studies have explored these relationships together, contributing to the literature on strategic management and Islamic finance.